Linguistic enablers of Pākehā racism: Excuses from the health sector in Aotearoa New Zealand - Heather Came; Toni Shepherd; Tim McCreanor; Dougal Thorburn (Journal of Critical Public Health)
Racism is a modifiable determinant of health that permeates the practices, relationships and environments of the health sector. Having produced and maintained grievous health disparities and injustices for generations, racism has done harm to the wellbeing of communities that is well understood but under-acknowledged. Questions arise as to how racism continues to flourish. We argue that everyday relational discourses within the health sector, especially explanations used by people in clinical, public health and bureaucratic roles, maintain systemic and localised inaction in the face of injustice. In this commentary we curate sets of excuses for racism garnered from our cumulative experience and organise them into narratives: i) resource allocation, ii) responsibility, iii) Māori blaming, iv) too hard, and v) we tried. We highlight the power of words in promoting racist agendas, but also the value of identifying such usage and acting to change the discourse toward an antiracist future. We believe these excuses or similar may be used in other settler-colonial contexts.